Semantic congruency and the Colavita visual dominance effect. - Koppen, C; Alsius, A; Spence, C (2008)
Participants presented with auditory, visual, or bimodal audiovisual stimuli in a speeded discrimination task, fail to respond to the auditory component of bimodal targets significantly more often than to the visual component, a phenomenon known as the Colavita visual dominance effect. Given that spatial and temporal factors have recently been shown to modulate the Colavita effect, the aim of the present study, was to investigate whether semantic congruency also modulates the effect. In the three experiments reported here, participants were presented with a version of the Colavita task in which the stimulus congruency between the auditory and visual components of the bimodal targets was manipulated. That is, the auditory and visual stimuli could refer to the same or different object (in Experiments 1 and 2) or audiovisual speech event (Experiment 3). Surprisingly, semantic/stimulus congruency had no effect on the magnitude of the Colavita effect in any of the experiments, although it exerted a significant effect on certain other aspects of participants' performance. This finding contrasts with the results of other recent studies showing that semantic/stimulus congruency can affect certain multisensory interactions.